2018
DOI: 10.1186/s12916-018-1152-1
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the impact of social groups and vaccination on inequalities in infectious diseases using a mathematical model

Abstract: BackgroundSocial and cultural disparities in infectious disease burden are caused by systematic differences between communities. Some differences have a direct and proportional impact on disease burden, such as health-seeking behaviour and severity of infection. Other differences—such as contact rates and susceptibility—affect the risk of transmission, where the impact on disease burden is indirect and remains unclear. Furthermore, the concomitant impact of vaccination on such inequalities is not well understo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…Mathematical modeling studies of social disparities in influenza burden have used a simulation approach [27][28][29] and have focused on the effects of material deprivation (i.e. lack of access from income, education, and employment) or social deprivation (i.e.…”
Section: Plos Computational Biologymentioning
confidence: 99%
See 1 more Smart Citation
“…Mathematical modeling studies of social disparities in influenza burden have used a simulation approach [27][28][29] and have focused on the effects of material deprivation (i.e. lack of access from income, education, and employment) or social deprivation (i.e.…”
Section: Plos Computational Biologymentioning
confidence: 99%
“…Such studies are important in uncovering the mechanistic explanations of influenza disparities, but have been limited in their geographical extent, or by the use of proxy measures. For example, [ 27 , 29 ] consider phenomenological variation in social contact rates without empirical evidence linking vulnerable groups to that variation, thus limiting insights on the mechanisms that lead to influenza disparities; [ 28 , 29 ] focus on dynamics within specific cities, limiting generalizability.…”
Section: Introductionmentioning
confidence: 99%
“…Mathematical modeling studies of social disparities in influenza burden have used a simulation approach [27, 28, 29] and have focused on the effects of material deprivation (i.e. lack of access from income, education, employment) or social deprivation (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Such studies are important in uncovering the mechanistic explanations of influenza disparities, but have been limited in their geographical extent, or by the use of proxy measures. For example, [27, 29] consider phenomenological variation in social contact rates without empirical evidence linking vulnerable groups to that variation, thus limiting insights on the mechanisms that lead influenza disparities; [28, 29] focus on dynamics within specific cities, limiting generalizability.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of the initial weeks of the vaccination programme in England highlights emerging inequalities in vaccine coverage with lower rates in ethnic minorities, people living in areas of higher deprivation, and those with severe mental illness or learning disabilities ( 4 ). This is concerning but unsurprising as previous research has shown that universal interventions can increase inequality because of the differential uptake between communities ( 5 , 6 ).…”
mentioning
confidence: 97%